Fabrication and testing of bagasse particle reinforced biocomposite - Selvam, R. (Universiti Malaysia Sarawak, UNIMAS, 2010)
Bagasse is the residue of sugar cane after the juice extraction process. With the increase in sugar cane plantation due to the demands of sugar milling industry, bagasse is also produced in large quantity. Rather than allowing this large amount of bagasse to go to waste, it is more rational to make good use of this material. In this study, the potential of bagasse to be used as biocomposite’s reinforcement material is analyzed. This is done by analyzing the mechanical properties of the composite. The effect of particle weight fraction towards the mechanical properties of the composite is also analyzed and discussed. To obtain the mechanical properties data of the composite, three mechanical tests were carried out in accordance with ASTM standards. The tensile strength and Young’s modulus value increases with increasing bagasse particle weight fraction. However, the flexural strength and hardness value decreases with increasing bagasse particle weight fraction. The overall outcome is satisfactory as the objective of this study is achieved. There are still a few improvements that can be applied to improve the mechanical properties of the bagasse biocomposite.